Image Processing and Model Based Arc Detection in Pantograph Catenary Systems - Yaman, Orhan; Karakose, Mehmet; Aydin, Ilhan; Akin, Erhan (Ieee, 2014)
A pantograph-catenary system transmits the electric energy that an electrified train needs from electric power substation to train. Pantograph catenary system is extremely important in order to carry out continuous of the transmission. In this study, a model and image processing based arc detection system is proposed. Arcs occurred in a video frame are detected by using image processing techniques. Data obtained from a sequence of frames are used to model the arc. Arcs occurred in image sequences are modelled during modeling stage. As consequence of the modeling, current and voltage signals, which belong to healthy and arc occurred conditions, are obtained. These signals are analyzed to detect the condition of the pantograph-catenary system as healthy or faulty. S-transform is applied to these signals and occurred arcs are detected.
Pantograf katener sistemlerde görüntü işleme ve model tabanli ark tespiti
22nd IEEE Signal Processing and Communications Applications Conference (SIU) -- APR 23-25, 2014 -- Karadeniz Teknik Univ, Trabzon, TURKEY
Keywords: pantograph catenary systems; image processing; Mayr arc model; S transforms; arc detection